The assessment of long-wavelength gravity field from GOCE based Global Gravitational Model (GGM) case study : Johor region - Wan Sabariah W Derapha @ Wan Mustapha, 1992-, author; Zainal Abidin Md. Som, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2015